Advancing production of marine fish in the United States: Olive flounder, Paralichthys olivaceus, aquaculture - John D. Stieglitz; Ronald H. Hoenig; Jenna K. Baggett; Carlos E. Tudela; Shubham K. Mathur; Daniel D. Benetti (Wiley, 2025)
The potential for marine aquaculture development in the United States is significant and recent factors have highlighted the benefits of developing a shortened seafood supply chain to service domestic markets. Marine finfish in particular hold tremendous potential as technological advancements, improvements in production efficiencies, and market forces have aligned to create opportunities for growth within this sector of the aquaculture industry. Olive flounder, Paralichthys olivaceus, also commonly known as the Japanese flounder or hirame, is a candidate species for the U.S. aquaculture industry, which has a demonstrated track record of culture success and high market value. Although cultivation of the species is novel to the United States, olive flounder has been produced commercially for decades in other regions, notably Korea and Japan. With a number of favorable production characteristics, including a relatively short growout time compared with other flatfish species, an efficient food conversion ratio, and a wellestablished market presence, the species has been shown to be commercially viable. This study examines the opportunities for olive flounder to be developed in the United States, while also discussing the potential for land-based recirculating aquaculture systems culture of this species in coastal areas to provide increased resilience for working waterfront communities